Central Sets Theorem for Arbitrary Adequate Partial Semigroups - Hindman, Neil; Pleasant, Kendra (Topology Proceedings, 2020)
We establish a Central Sets Theorem valid for arbitrary adequate partial semigroups. Except for the requirement that the sequences considered be adequate, it is identical to the currently most general version of the Central Sets Theorem for semigroups. We present an application to the partial semigroup of located words and obtain several related results.